Genetic analysis of impulsive personality traits: Examination of a priori candidates and genome-wide variation. (January 2018) - Gray, Joshua C.; MacKillop, James; Weafer, Jessica; Hernandez, Kyle M.; Gao, Jianjun; Palmer, Abraham A.; de Wit, Harriet
Abstract: Impulsive personality traits are heritable risk factors and putative endophenotypes for addiction and other psychiatric disorders involving disinhibition. This study examined the genetic basis of impulsive personality traits, defined as scores on the Barratt Impulsiveness Scale (BIS-11) and the UPPS-P Impulsive Behavior Scale (UPPS-P). In 983 healthy young adults of European ancestry, the study examined genetic variation in relation to a combined phenotype of seven subscales based on high phenotypic intercorrelations. The study first tested 14 a priori loci that have previously been associated impulsive personality traits or closely related constructs. Second, the study included an exploratory genome-wide scan (i.e., GWAS), acknowledging that only relatively large effects would be detectable in a sample size of 1000. A priori SNP analyses revealed a significant association between the combined impulsivity phenotype and two SNPs within the 5-HT2a receptor gene ( HTR2A ; rs6313 and rs6311). Follow-up analyses suggested that the effects were specific to the Motor and Non-planning subscales on the BIS-11, and also that the two loci were in linkage disequilibrium. The GWAS yielded no statistically significant findings. This study further implicates loci within HTR2A with certain forms of self-reported impulsivity and identifies candidates for future investigation from the genome-wide analyses. Highlights: A multivariate genetic analysis is applied to impulsive personality traits (IPTs). Significant loci within the HTR2A gene are identified. Doubt is cast on many previously identified candidate loci for IPTs. The GWAS results highlight suggestive candidates for future investigation.